Native-to-invasive rodent species turn-over within African cities: The example of Niamey, Niger - Abdoulaziz Ibrahim Danzabarma; Karmadine Hima; Madougou Garba; Seydou Issaka; Gauthier Dobigny (PLoS ONE, 2025)
Expanding transportation infrastructure has facilitated the introduction and proliferation of invasive small mammals, particularly now cosmopolitan rodents like Rattus spp. and Mus musculus, within urban socio-ecosystems where they may severely impact local biodiversity, economy and public health. However, fine-scale dynamics of such biological invasions are still poorly documented, especially in African cities where such biological invasions are still ongoing. We took advantage of a long-term monitoring program of terrestrial small mammal communities of Niamey, the capital city of Niger, to compare rodent and shrew faunas at the same sampling points ten years apart, namely in 2009–2013 and in 2020–2023. We show that Rattus rattus has been expanding significantly in almost all trapping areas across the city, while Mastomys natalensis relative abundance has decreased. This clear trend of native-to-invasive rodent species turnover was particularly marked within the core city, but some notable exceptions exist in peripheral as well as traditionally built zones where the native species still remains dominant. These patterns are discussed, with special attention given to possible human socio-economic and health implications.